망원경식 렌즈미터를 사용한 Wet Cell 방식의 친수성 콘택트렌즈의 정점굴절력 측정에 관한 정확도 연구 - 송경석; 이민제; 김태훈; 성아영 (대한시과학회지, 17(4), 2015)
목 적: 친수성 콘택트렌즈의 굴절력 측정 방식 중 하나인 Wet Cell 측정법에 대한 정확도를 확인하기 위해 망원경식 렌즈미터를 사용하여 콘택트렌즈의 정점굴절력을 측정하였다. 방 법: Wet Cell 측정용 홀더는 현재 임상에서 주로 사용하고 있는 Poster Soft Contact Lens Wet Cell 제품을 사용하였으며, 국내 제조업체의 렌즈를 함수율은 38%, 45%, 58%로 구면굴절력은 -3.00D, -7.00D, -10.00D로 분류하여 각각 실험하였다. 결 과: 망원경식 렌즈미터를 사용하여 Wet Cell 방식으로 콘택트렌즈의 정점굴절력을 측정한 결과, -3.00D의 콘택트렌즈는 함수율 38%일 경우 -3.41D로 45%일 경우 –3.41D로 그리고 함수율 58%일 경우 -2.63D로 각각 측정되었다. -7.00D의 콘택트렌즈는 함수율 38%일 경우 –7.87D로 45%일 경우 –7.20D로 그리고 58%일 경우 -5.19D로 각각 측정되었다. 또한 -10.00D의 콘택트렌즈는 함수율 38%일 경우 –10.17D로 45%일 경우 -10.60D로 58%일 경우 -7.33D로 각각 측정되었다. 결 론: 실험 결과, 함수율이 높을수록 Wet Cell 방식에 의한 측정값은 콘택트렌즈에 표기된 굴절력에 비해 낮게 측정되는 경향을 나타내었다. 디옵터가 높아질수록 측정 정확도 역시 신뢰도가 낮은 것으로 나타났다. Wet Cell 방식을 사용하여 망원경식 렌즈미터로 측정 시 함수율과 디옵터별로 정확도의 차이가 발생됨을 알 수 있었다. Purpose: The purpose of this study is to verify the accuracy of vertex refractive power of contact lenses by using telescope type lensmeter by wet cell method. Method: The used wet cell is from method Post Soft Contact Lens Wet Cell. The contact lenses with water content ratio of 38%, 45% and 58% were measured with spherical power of -3.00D, -7.00D and -10.00D respectively. Result: Using wet cell method with manual lensmeter, the spherical power of -3.00D contact lens with water content ratio of 38% was measured as -3.41D. And the contact lens with water content ratio of 45% was measured as -3.41D identically. However, in case of the contact lens with 58% of water content ratio was measured as -2.63D. The -7.00D contact lens was measured as -7.87D when water content ratio was 38%, -7.20D when water content ratio was 45%, and -5.19D when water content ratio was 58%. Finally, the -10.00D contact lenses with water content of 38%, 45% and 58% was measured as –10.17D, -10.60D and –7.33D respectively. Conclusion: The contact lenses with high water content were measured inaccurately reflecting a significantly lower diopter measurement. This tendency was pronounced even more with highly minus powered contact lenses with high water content ratio. The contact lens measurement using manual lensmeter with wet cell method reflected notable difference highly depending on the water content ratio and diopter. KCI Citation Count: 0